Monoclonal Cell Line Generation and CRISPR/Cas9 Manipulation via Single‐Cell Electroporation. Issue 12 (12th February 2018) - Yang, Ruiguo; Lemaître, Vincent; Huang, Changjin; Haddadi, Abbas; McNaughton, Rebecca; Espinosa, Horacio D.
Abstract: Stably transfected cell lines are widely used in drug discovery and biological research to produce recombinant proteins. Generation of these cell lines requires the isolation of multiple clones, using time‐consuming dilution methods, to evaluate the expression levels of the gene of interest. A new and efficient method is described for the generation of monoclonal cell lines, without the need for dilution cloning. In this new method, arrays of patterned cell colonies and single cell transfection are employed to deliver a plasmid coding for a reporter gene and conferring resistance to an antibiotic. Using a nanofountain probe electroporation system, probe positioning is achieved through a micromanipulator with sub‐micron resolution and resistance‐based feedback control. The array of patterned cell colonies allows for rapid selection of numerous stably transfected clonal cell lines located on the same culture well, conferring a significant advantage over slower and labor‐intensive traditional methods. In addition to plasmid integration, this methodology can be seamlessly combined with CRISPR/Cas9 gene editing, paving the way for advanced cell engineering. Abstract : Monoclonal cell lines are generated via single‐cell electroporation using a nanofountain probe transfection system and arrays of patterned cell colonies. The method eliminates the time‐consuming and labor‐intensive limiting dilution process, often used in current cell line generation techniques, and can be seamlessly combined with CRISPR/Cas9 gene editing tools.